(untitled) (The Pakistan Development Review, 2007)
Modern macroeconomics literature emphasises both the short run and long run objectives of fiscal policy [Romer (2006)]. In the short run it can be used to counter output cyclicality and/or stabilise volatility in macro variables, which is descriptively same as of effects of the short run monetary policy. Further for the long-run, fiscal policy can also affect both the demand and supply side of the economy. But in most traditional analyses it is assumed that fiscal policy would adjust to ensure the intertemporal budget constraint to be satisfied, while monetary policy is free to adjust its instruments [‘Ricardian Regime’ by Sargent (1982)] such as stock of money supply or the nominal interest rate [Walsh (2003)]. The debt financing methods, expenditure and tax powers of fiscal authorities i.e. the fiscal policy has also been seen as to affect both the supply and demand side of the economy. As noted by Baxter and King (1993), the initial Real Business Cycle models had only the supply side effects of the fiscal policy, where these were transmitted through the wealth effect and labourleisure choices of the household. Recently also New-Keynesian type models with micro-foundations and sticky prices argue that still through the supply side fiscal policy management could be accorded for stabilisation [Linnemann and Schabert (2003)]. The demand side effects of the fiscal policy could also be found only with more imperfections such as ‘Rule of Thumb’ consumers or those with liquidity constraints, which lead to exclusion of Ricardian equivalence [Gali, et al. (2005)]. But all that depends on the structure of the economy, as Blanchard and Perotti (2002) stated: